GAYA HIDUP PELAJAR SMA YANG MENGGUNAKAN MOBIL PRIBADI KE SEKOLAH (STUDI PADA SISWA – SISWI SMA ISLAM AS-SHOFA PEKANBARU) - Sari, Putri Nurul; Yusuf, Yusmar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In the current era of globalization a human face various challenges to be able to move faster in every respect. Life spins under the influence of science, technology, and rational thinking. Habits slowly began to change and create new habits into one's lifestyle. Each group in a given social structure will have a distinctive lifestyle that has become a symbol of prestige in social stratification. David Chaney (1996: 41) assumes that the lifestyle of a modern world, or it could be called modernity. Or it could be called modernity. The point is that anyone living in modern society will use the idea of the lifestyle to describe his own actions as well as others. Worries many people in our neighborhood who look exclusively on that adequate facilities at high school teenagers will present a hedonistic man, not merely consumptive but also in the utilization of spare time. However, such concerns is inversely proportional to that of the author who saw inclusively lifestyle of students take a private car to school at SMA Islam As-Shofa this. Male and female students at an Islamic school creates its own habits that become a way of life, both in the utilization of the effective time, the use of facilities owned, until the behavior and attitude of daily life. The method used in this paper is a quantitative descriptive. Where all the data collected and grouped according to the group of students and student then explained using figures that later interpreted quantitative descriptive.Keywords: Car, High School Student, Lifestyle